Patient reporting of outcomes following elective surgery to remove gallbladder - Chew, Woon Ling (2017)
Background Patient-Reported Outcome Measures (PROM) play a significant role in understanding patients’ perceptions while moving to a patient-centric healthcare system. Studies have shown that gallbladder diseases are a common occurrence in the population. Meanwhile, there are studies related to the cholecystectomy outcomes including hospital stay, cost of the treatment, day-case surgery, and commissioning guide available for gallbladder disease. However, this is insufficient to show that the guidelines and surgical outcomes that implemented by policymakers are important to patients, especially in Singapore. Objective Hence, this study aims to identify the possible factors that are most valued by patients who underwent elective gallbladder removal surgery in Singapore. Methodology A PROM analysis was performed on 75 respondents who underwent the elective gallbladder removal surgery from 7th August 2017 – 31st October 2017 in TTSH. Results Overall, the two most valued factors in patients have been identified from different aspects accordingly. Majority of the patients considered the experience level of the surgeon and quality of life as the most significant factors following elective gallbladder removal surgery. Conversely, the period of medical certificate and length of hospital stay were not their main concern. Conclusion This study is important for healthcare professionals and policymakers to further understand patients’ perception towards elective gallbladder removal surgery in order to formulate strategies to suit patient needs and hopefully, enhance the patient care and healthcare system in Singapore.